Life Skills Development for Students Through Entrepreneurship - Nirwana Suciyati; Baharuddin Baharuddin; Mardhiah Mardhiah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to: (1) analyze the development of students’ life skills through entrepreneurship at Le Cendekia Nature School; (2) identify the supporting and inhibiting factors in the implementation of life skill development; and (3) examine the impact of entrepreneurship-based programs on students’ character and competence. This research uses a qualitative descriptive method with pedagogical, educational management, and psychological approaches. Data were collected through observation, interviews, and documentation involving the school principal, life skill coaches, and students. The findings indicate that life skills are fostered through entrepreneurship activities such as ecoprinting, food processing, and the use of local natural resources, all designed as project-based learning. The implementation emphasizes experiential and contextual learning with strong mentoring. Supporting factors include the alignment of school vision and policies, availability of natural resources, and parental involvement. Meanwhile, inhibiting factors consist of limited facilities, a lack of advanced training for teachers, and insufficient access to broader markets. This study concludes that the integration of entrepreneurship into life skill education provides a strategic framework for shaping independent, responsible, and confident learners. These findings may serve as a reference for developing contextual and sustainable entrepreneurship curricula in nature-based educational institutions.